ПСИХОЛОГО-ПЕДАГОГІЧНІ ПЕРЕДУМОВИ ТА ЗАКОНОМІРНОСТІ УПРАВЛІННЯ ЕФЕКТИВНИМ РОЗВИТКОМ ОСОБИСТОСТІ УЧНЯ в ОСВІТНЬО - ВИХОВНОМУ ПРОЦЕСІ (Педагогіка вищої та середньої школи, 2022)
The article deals with psychological and pedagogical preconditions and original laws of governing the effective development of pupil’s personality in the process of education.